ADDITION OF CHLOROQUINE DIPHOSPHATE OR ASCORBIC ACID IN JERSEY BULL SEMEN AND SUBSEQUENT EVALUATION WITH RESPECT TO POST-THAW INCUBATION TIME AND CONCEPTION RATE - SINGH, MADHUMEET; SHARMA, A (The Indian Journal of Animal Reproduction, 2022)
Total 36 ejaculates (6 from each Jersey bull) were used in the study and aliquots were added with Chloroquinediphosphate or Ascorbic acid or served as control. Semen straws from all the groups were analyzed at 0, 1and 2 h post-thaw incubation at 37°C for percent viability, progressive motility, reaction to hypo-osmotic solutionand acrosomal integrity. Following post-thaw incubation, an improvement (p
Keywords: Acrosomal integrity; Ascorbic acid; Chloroquine diphosphate; Conception rate; HOST